The influence of the international non-state on the strategies of diplomacy: an approach from public communication (Comillas Journal of International Relations, 2016)
The proliferation of non-state actors is gradually transforming diplomacy relations: they challenge traditional sovereignty-based notions in favour of alternative configurations built around shared values and transnational issues. Non-state actors exert a power of influence that advices adaptation of traditional diplomacy in order to properly deal with them. Although their legitimacy to develop diplomatic activity is controversial, the hypothesis expressed in the present work assumes that nonstate actors’ legitimacy to intervene in international politics lies on their effectiveness in contributing to address global threats and on their representativeness by expressing citizenry concerns. Both, effectiveness and representativeness, depends largely on non-state ability to manage public communication. The communicational ability consists in disseminating a convincing discourse, in communicating coherently with their identity, and in shaping narratives to get public support. The analysis offers some insights to guide a transformation of diplomacy relations in order to take advantage of synergies by dealing with different players.
Keywords: Non-state actors; diplomacy; public diplomacy; public communication; strategic communication